Citrus fruits intake and oral cancer risk: A systematic review and meta-analysis. (July 2018) - Cirmi, Santa; Navarra, Michele; Woodside, Jayne V.; Cantwell, Marie M.
Graphical abstract: Abstract: Objective: To quantify the relationship between Citrus intake and risk of cancer of the oral cavity and pharynx. Design: Systematic review and meta-analysis. Data sources: Ovid MEDLINE, EMBASE, and Web of Science were searched until September 2017. Search terms included Citrus, Citrus aurantifolia, Citrus sinensis, Citrus paradisi, Citrus fruits, Citrus fruits extract, Citrus oil, fruits, oral cancer, mouth cancer, mouth neoplasm. Study selection: The selection of studies and the systematic review were carried out in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. A pre-defined inclusion checklist resulted in the inclusion of articles which were (i) published in peer-reviewed scientific journals; (ii) English language; (iii) and included a measure of Citrus fruit intake and risk of oral and pharyngeal cancer. Studies were excluded if (i) preparations derived from other fruits were used, (ii) Citrus intake was combined with intake of other fruits; (iii) in vitro or animal models were used. We also excluded reviews, systematic reviews, meta-analyses, letters, personal opinions, conference abstracts and book chapters. Data extraction: Three reviewers independently performed the extraction of data from studies included. Results: Seventeen studies met our inclusion criteria and were included in the final review. Pooled analyses showed that those with the highest Citrus fruit intake compared to the lowest intake had a 50% reduction in risk of oral cavity and pharyngeal cancer (OR 0.50; 95% CI 0.43–0.59). Conclusion: The studies included in this review and meta-analysis showed an inverse association between Citrus fruit intake and oral cancer.